The historical development of critical school psychology in Brazil - Firbida, Fabíola Batista Gomes [UNESP]; Vasconcelos, Mário Sérgio [UNESP] (My University, 2018)
We present in this article some considerations about evidences of the historical development of the criticism movement on school psychology in Brazil. The process began in the 1980s and sought to break with the stance of traditional school psychology which, supported by the clinical medical model, used to classify and correct students with learning difficulties. This is a bibliographical research that aimed to analyze an emerging form of psychology that was concerned with giving a new direction in the school area and identify the historical and social roots of psychology and education. The main strand of this movement took place through a model of criticism to capitalist society with respect to its harmful effects on school education. Authors who rely on the method of historical-dialectical materialism stood out. We noticed that although this critical perspective has not been developed at the theoretical level, it is still under constructionin the practical field.
O desenvolvimento histórico da psicologia escolar crítica no Brasil
Keywords: Critical school psychology in Brazil; History of psychology; School psychology